From Prompts to Progress: Leveraging Generative AI in College English Writing Instruction - Yuchun, Xie (INTI International University, 2025)
With the rapid rise of large language models like ChatGPT, generative AI (GenAI) is transforming language education. This study investigates prompt engineering in a college English writing course, showing how structured prompts scaffold the writing process. By aligning prompt types with stages of academic writing, the framework systematizes GenAI use and extends theories of scaffolding and meta-cognition. Findings indicate that prompts enhance engagement, support evidence-based argumentation, and enable recursive writing via real-time feedback. Compared with conventional teacher feedback, the model fosters autonomy, reflection, and frequent revisions, offering theoretical and practical insights for AI-supported L2 writing and sustainable English teaching.